Efektivitas Program Keluarga Berencana BKKBN Provinsi Banten dalam Mewujudkan Keluarga Berkualitas di Kota Serang - Irna Fajriah; Nurikah Nurikah; Ahmad Lanang Citrawan (Perspektif Administrasi Publik dan hukum, 2025)
This research is motivated by the problem of the effectiveness of the BKKBN Banten Province family planning program in realizing quality families in Serang City based on Law Number 52 of 2009 concerning Population Development and Family Development. The identification of the research problem is how effective is the BKKBN Banten Province KB program in efforts to realize quality families in Serang City? and what are the factors that influence the effectiveness of the BKKBN Banten Province KB program and solutions in facing obstacles to realizing quality families in Serang City. The theory used is the theory of legal effectiveness and the theory of the welfare state. The method used is empirical juridical, the research specifications used are descriptive qualitative. Using research data sources in the form of primary data and secondary data. Meanwhile, the data collection technique used in this study uses literature studies and field research. The data analysis used is a qualitative descriptive approach. The results of this study indicate that the family planning program from the BKKBN of Banten Province has been quite effective in realizing quality families in Serang City. The conclusion of this study is that the effectiveness of the KB program in realizing quality families in Serang City is quite effective, this is based on a review of the effectiveness of law from Soerjono Soekanto on five aspects of legal effectiveness, namely legal factors, law enforcement, facilities and infrastructure, society, and culture. However, it still faces obstacles in cultural factors and its society. In addition, the iBangga value in Serang City is 53.41, which indicates that Serang City is in the fairly good (developing) category. This study shows the role of the government in improving the welfare and quality of life of the community. In this case, in an effort to fulfill social services through the BKKBN Banten Province family planning program which aims to realize quality families in Serang City. The obstacles faced require improvements in the legal culture factor that needs to be improved with education and socialization in order to build awareness of the Serang City community about the importance of following the family planning program in realizing quality families in Serang City.